Evaluation of clonidine as an adjuvant to brachial plexus block and its comparison with tramadol - Prakash Kelika; Jamkar Maya Arun (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: It has been reported that clonidine when used as an additive in a dose of 90 μg in adults increases the duration of peripheral nerve blocks. Hence, this study was conducted to evaluate the effect of clonidine in brachial plexus blocks and to compare it with tramadol. Material and Methods: Ninety patients posted for upper limb orthopedic surgery were divided randomly into three groups. 40 mL of local anesthetic solution was prepared using 15 mL of 2% lignocaine-adrenaline-sodium bicarbonate solution, 15 mL of 0.5% bupivacaine, and 10 mL distilled water. Patients received a supraclavicular brachial plexus block with 0.7 mL/kg of this solution to which either 1 mg/kg tramadol, 1 μg/kg clonidine, or 1.5 μg/kg clonidine was added. The onset and duration of sensory and motor block and the duration of postoperative analgesia were recorded. Pulse rate, blood pressure, respiratory rate, saturation, sedation, and any side effect were monitored. Results were statistically analyzed using analysis of variance F-test and unpaired t-test. Results: There was a statistically significant difference in the onset of both the sensory and motor components of the block with the fastest onset seen when clonidine was used in a dose of 1.5 μg/kg. The block also lasted statistically significantly longer with clonidine as compared with tramadol although there was no statistically significant increase in the duration of the block when a higher dose of clonidine was used. The time for rescue analgesia was the longest in patients who received 1.5 μg/kg of clonidine (491.8 ± 33.9 min). This duration was also statistically significant. Patients who received tramadol reported a statistically significant higher incidence of nausea. Conclusion: Clonidine in a dose of 1.5 μg/kg body weight provided the fastest onset of sensory as well as motor block and the longest duration of postoperative analgesia and thus is a good additive to local anesthetic solutions for brachial plexus blocks.